Factors influencing purchase intention of packaged food among adults in Klang Valley, Malaysia / Zahira Aqila Nordin and Teo Swee Sen - Nordin, Zahira Aqila; Teo, Swee Sen (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA Selangor, Puncak Alam Campus, 2024)
Internal and external factors can influence individual interpretation and selection of packaged food. This paper aims to determine factors influencing consumers' purchase intention of packaged food (product taste, packaging, ingredients, nutritional value, price, brand, Halal label, advertisement, country of origin, and promotional scheme) among adults in Klang Valley, Malaysia. A total of 300 respondents participated in the online questionnaire survey through the convenience sampling method. Descriptive statistical and factor analyses were used to examine the data and determine the factors’ rank order. Data showed individual habits, attitudes, perceptions, and socio-demographic factors (gender, age, education level, household income, and marital status) affect a consumer's purchase intention. The majority of consumers of packaged food were employed (76.7%). Consumers are drawn to packaged food because it is convenient (42.8%) and delectable (31.1%). The main findings of this study demonstrate that the selected factors have been grouped into four primary categories: sales deriving factor (23.8%), informational factor (14.9%), taste-related factor (12.2%), and quality assurance factor (10.5%). This research may aid in providing consumer insights that benefit food manufacturers or marketers in the efforts to create or improve packaged food products per consumers' preferences.